READING TOPICS NEEDED BY THE STUDENTS OF ISLAMIC EDUCATION DEPERTMENT FOR THE CONTENT-BASED READING INSTRUCTIONAL MATERIAL - Amin, Syarif (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This study aims at developing reading instructional material using content-based instruction (CBI) approaches for the students of Islamic Education Department in a private university in Southeast Sulawesi province. This is a research and developmental research with ADDIE developmental model. This study involved the lecturers and students of Islamic Education Department. This paper presents the result of preliminary studies (need analysis) related to the reading topics needed by the students in learning English. The data were obtained through questionnaires and interviews. From the results of the need analysis it was found that the priority reading topics needed by the students of Islamic Education Department are: Good Morals in Islam (3.68); The ‘Ibadah in Islam (3.65); Hijab in Islam (3.65); The Source of Islamic Teaching (3.6); Jihad in Islam (3.55) The Aqidah in Islam (3.47).